Presentation - Zanin, Larissa Fabrício (Farol, 2024)
In honor of the 30th anniversary of the Capixaba Seminar on Art Education, Revista Farol brings together, in this commemorative edition, texts by artists, teachers and researchers who address contemporary themes and issues for art and its teaching. Issues of gender, race, class and diversity permeated the debates held at the 15th Capixaba Seminar on Art Education, whose theme “Urgent Dialogues” brought to light the need to reflect and propose new educational practices in art not only in methodological terms, but also in epistemological terms.